Endoxifen in the management of behavioral addiction – A case report exploring its use beyond mood stabilization - Choudhary, Dnyanraj; Karwa, Rupali (Indian Journal of Case Reports, 2026)
Impulsivity is one of the core features of behavioral addiction. Recent evidence suggests a role of increased protein kinase C (PKC) activity in the pathophysiology of impulsivity. Consequently, it has been hypothesised that endoxifen, a direct PKC inhibitor, may be useful in the management of impulsivity. We report the case of a 29-year-old woman with a 5–6-year history of impulsive high-risk behaviors in the form of dating-app overuse, substance use, and mood symptoms such as impaired self-care, irritability, disturbed sleep, and appetite, for which she was diagnosed to have a mood disorder with behavioral addiction. Addition of endoxifen at a dose of 8 mg/day led to marked improvement in impulsivity, cravings for substances, and mood symptoms, with good tolerability and sustained benefit over 3 months.